До питання механізмів біологічної дії магнітного поля 50 Гц - Назаренко, В.І. (Актуальні проблеми транспортної медицини, 2009)
Автором проанализировано влияние хронической экспозиции МП 50 Гц с уровнями 7, 250 и 7000 мкТл на свободно радикальные процессы и показатели ЕКГ у белых крыс. Наблюдаемые биологические эффекты можно пояснить следующими, описанными в литературе механизмами действия МП 50 Гц: параметрический резонанс иона Са2+ (порог действия 7 мкТл), влияние на свободно радикальные процессы (порог действия 250 мкТл), возникновение наведенных токов (порог действия 7000 мкТл). It was analyzed the influence of a chronic exposure of MF 50 Hz with levels 7, 250 and 7000 mkT on free radical processes and parameters of ECG on white rats. The observable biological effects could be explained by the following, described in the literature, mechanisms of MF 50 Hz action: parametric resonance of ion Са2 + (threshold of action 7 mkT ), influence on free radical processes (threshold of action 250 mkT), occurrence of induced currents (threshold of action 7000 mkT).